DEVELOPMENT TRENDS, PROBLEMS AND CHALLENGES OF WINE TOURISM - Sopio Tsetskhladze; Lali Osadze (Соціальна економіка)
The purpose of the article is to study wine tourism: wine and its accompanying products as the main means of attracting wine tourists. The importance of wine tourism in all tourism is highlighted by the trend of their increasing presence. The study is based on the experience of countries distinguished by wine tourism, data from international and local organizations, and a discussion of the current situation in Georgia. As a result of the analysis, it was determined that in countries known for wine tourism, wine and its accompanying products are one of the important means of attracting tourists and development of business. It is recognized that the wine tourism industry is one of the leading and most modern industries in the world, which is successfully used for economic development by countries that are prominent in this field. Wine is strongly linked to cultural and culinary heritage, the environment and the economy. An important factor contributing to the development of wine tourism is the organization of wine tours and wine festivals. International events, conferences, festivals organized by the United Nations World Tourism Organization contribute to the popularization of wine tourism and Georgian wine. In Georgia, more attention has recently been paid to the quality of wine, which strengthens the country's image as a quality wine producer in the world. Georgian qvevri wine has been included in the list of cultural heritage by UNESCO. The International Organization of Vine and Wine has included 8 Georgian wines in the list of special wines of the world. Attention is drawn to the opinion of specialists about Georgian wine. They note the special taste qualities of Georgian wine, its ancient history and culture. This fact contributes to attracting tourists and developing wine tourism.   It has been proved that state support and various marketing events play a major role in achieving success. In the process of research, quantitative and qualitative research methods are used, appropriate analysis is made. As a result of the research, the research hypothesis was confirmed, a conclusion was formed and recommendations were developed. The expressed opinions and recommendations are important for field specialists, scientists and all interested persons.